Analysis of Learning Effective Improvement through the Application of Digital Literature in Learning in Kristen Rantepao SMA - Hendrik Palinggi; Mesta Limbong; Lisa Gracia Kailola (Budapest International Research and Critics University, 2022)
The aims of this research are 1) to be able to find strategies to improve teacher pedagogic competence in implementing digital literacy; 2) to improve the aspect of collaboration between students so that they can collaborate in learning with the implementation of digital literacy; 3) to improve aspects of students' attention in learning by implementing digital literacy; 4) to improve the aspect of student interest/curiosity in learning with the implementation of digital literacy; 5) To improve the communication aspect of students in learning by implementing digital literacy; 6) To improve aspects of student creativity in learning by implementing digital literacy. The method used is qualitative with a participatory action research (PAR) approach. The results obtained: 1) the benefits of digital literacy in the aspects of cooperation and teacher pedagogical competence are the sharing of resources through social media (WhatsApp, Telegram, messenger) or e-mail; 2) With digital literacy, teachers can present more concrete digital media in learning; 3) It is easy to obtain information from digital sources so that the information obtained by students is always updated so that students are more communicative and open in learning; 4) The presence of digital teaching materials that are more interesting and interactive makes the desire/curiosity of students increase so that students are more active in learning and become independent learners; 5) The existence of various interactive media, digital learning resources, and innovative findings on the internet that are easily accessible through digital tools make student creativity increase along with the application of digital literacy; 6) The application of digital literacy in learning can run well if the teacher's pedagogic competence is good to guide students to learn digitally according to their abilities and interests.